SPIRIT AT WORK FROM WORK MOTIVATION ASPECTS, WORK DISCIPLINE AND PHYSICAL WORK ENVIRONMENT: EMPIRICAL STUDY - Fahrur Rozy; Purbo Jadmiko (Jurnal Ilmiah Ekonomi Dan Bisnis, 2023)
This study aims to determine the effect of work motivation, work discipline, and physical work environment on employee spirit at work at the Pariaman City Fire Department. This research was conducted at the Pariaman City Fire Department. The population in this study was 72 people. This sampling method is the census method. The type of data used is primary data through questionnaires. The data analysis method used is multiple linear regression analysis. The results showed that work motivation, work discipline, and physical work environment had a positive effect on work spirit at work. The implication that can be made from the results of this research is to continue to transform in terms of maintaining employee spirit at work. The proportion of respondents who are dominated by men is one of the limitations of the generalization of the results of the study.